KEY ISSUES OF CONTEMPORARY EDUCATIONAL POLICY AND PRACTICE - N. V. Popova (Высшее образование в России)
The main problems considered are the difficulties of interlinking Federal State Educational Standard with professional standards and compliance with the principle of regionalization in the development of independently established educational standards in linguistics. A brief analysis of the university's consultations with employers in the field of translation activities is given, which is aimed at formulating professional competencies if professional standard is not available. The complexities of the competence approach implementation in terms of the competence assessment are discussed, as well as the problems of student-centered learning within the framework of Bologna process and the organization of individual educational routes. The paper gives examples of methodological work with regulatory documents, illustrates innovative aspects in the practice of a modern university, in particular, the use of mobile modules, project training and MOOC courses as additional learning resources.